A democratic school: Teacher reconciliation, child-centred dialogue and emergent democracy. Issue 6 (24th November 2022) - Motherway, Gillen
Abstract: This article is an exploration of a democratic school where the author spent several years researching and engaging with teachers and students while investigating the practice of Philosophy for/with Children (P4C) within Irish Educate Together schools. I offer an account of how teachers in these contexts seek to reconcile and harmonise their P4C practice with their own educational and democratic outlooks. These perspectives were uncovered through a 'lived enquiry' study involving deep immersion in the day-to-day life of a school as a researcher and P4C practitioner. Teachers seeking to reconcile their practice with their views in this context resulted in the children in their classrooms learning through democratic processes, where democracy is not merely prescribed, but instead becomes a way of life. By drawing upon excerpts of teacher interview data from my doctoral studies, I suggest that there is a 'rough ground' of practice where diverse and unique perspectives can be revealed when lived, deeply immersive and sensitive approaches are taken towards practitioners and their communities. The intertwining of Educate Together and P4C philosophies of education is explored, with particular emphasis on the notion of child-centredness, dialogue and philosophical enquiry with children. Expanding on the democratic educational ideas of Biesta and Fielding, I argue that there is a deeply contextual and philosophically compelling connection between teachers engaging in P4C, the atmosphere or environment in which dialogue with children can occur and a different understanding of democracy through education that may result.